Qualitative dynamics of waxy maize (Jikenuo 19) in different harvest times (Bangladesh Journal of Botany, 2021)
Jikenuo 19 was used as experimental material, and six harvest times were set to study the effects of different harvest times on grain quality and gelatinization characteristics, so as to provide reference for the harvest time and quality improvement of waxy maize varieties. The results showed that when the harvest time was 27 days after pollination, the sensory and cooking quality score of Jikenuo 19 was the highest. Starch content increased with the delay of harvest time, while protein and soluble sugar content decreased. With the delay of harvest time, the peak viscosity, valley viscosity, final viscosity, disintegration value, recovery value and peak time all showed a trend of first increasing and then decreasing. Compared with starch and soluble sugar, the effect of protein in grain on gelatinization characteristics was higher. The present findings reveal that the best harvest time was 27 days after pollination, which will provide reference for determining the best harvest time and improving grain quality.Bangladesh J. Bot. 50(3): 987-992, 2021 (September) Special